Production of N-acylhomoserine lactone signal molecules by gram-negative soil-borne and plant-associated bacteria - Veselova, M; Kholmeckaya, M; Klein, S; Voronina, E; Lipasova, V; Metlitskaya, A; Mayatskaya, A; Lobanok, E; Khmel, I; Chernin, L (Folia microbiologica, 2003)
Quorum-sensing control mediated by N-acylhomoserine lactone (AHL) signal molecules has been established as a key feature in the regulation of various metabolic traits in many bacteria. Approximately 300 strains representing 6 genera and 18 species of soil-borne and plant-associated Gram-negative bacteria isolated in various regions of the former USSR using two reporter systems were screened for AHL production. The production was observed in 17.5% of the screened bacterial strains. Positive response was detected in all of the 14 tested strains of Erwinia herbicola, in 41 of the 239 strains of Pseudomonas species; in all 5 strains of Xanthomonas ampelina, X. campestris pv. malvacearum, pv. translucens, pv. vesicatoria and in one strain of Pantoea stewartii. AHL assay of 41 strains of X. maltophilia (syn. Stenotrophomonas maltophilia) isolated from soils with Chromobacterium violaceum reporter has revealed no strains synthesizing these signal molecules; 26 strains analyzed with Agrobacterium tumefaciens reporter showed the same result.
Keywords: gama-butyrolakton; rostliny; 4-Butyrolactone; signální transdukce; Signal Transduction; Soil Microbiology; Gram-Negative Bacteria; půdní mikrobiologie; gramnegativní bakterie; Plants